Analisis Yuridis Pemberhentian Sepihak Direksi Perseroan Terbatas Berdasarkan Putusan Mahkamah Agung Nomor 1888 K/Pdt/2020 - Syabrina, Erica Dwi (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2024)
Legal protection against unilateral termination of the direction of a Limited Liability Company (PT) through a General Meeting of Shareholders (GMS) is an important issue, as seen in the Supreme Court Decision Number 1888 K/Pdt/2020. This study analyzes legal protection as a direction terminated without clear reasons and the opportunity to defend itself. This study uses normative legal research with a case and regulatory approach. The results of the study show that the unilateral termination of the directors of PT Multi Daya Wonua was carried out verbally without a strong legal basis, so it is contrary to Law Number 40 of 2007 concerning Limited Liability Companies, especially Article 105 which stipulates that directors must be allowed to defend themselves before being dismissed. Although the court ruled that the GMS has the authority to dismiss, the decision did not consider aspects of justice and the right of direction. This can be justified as an unlawful act. Directors who are unlawfully terminated are entitled to legal protection in the form of cancellation of the GMS decision or compensation according to the remaining term of office. Therefore, fairer law enforcement and stronger protection for the direction are needed to prevent arbitrary actions in the management of PT.